Neural tube defect recurrence after 'partial' vitamin supplementation. Issue 5 (May 1989) - Sheppard, S; Nevin, N C; Seller, M J; Wild, J; Smithells, R W; Read, A P; Harris, R; Fielding, D W; Schorah, C J
Abstract : A total of 227 mothers enrolled for periconceptional multivitamin supplementation because of previous neural tube defect (NTD) births took vitamins for less than the recommended minimum period (at least 28 days before conception until two menstrual periods have been missed). Of 213 examined infants/fetuses born to these partially supplemented mothers, two had NTD, one of whom followed four previous NTDs. The observed NTD recurrence rate is similar to that observed in fully supplemented mothers. A further 14 mothers started supplements before the second missed period but after the normal time of neural tube closure. Three of their offspring had NTD. The significance of this apparently high recurrence rate is discussed.